Jeevaniya Mahakashaya: Ayurvedic and Pharmacological Insights – A Review - Brahma, Prachi; Kumar Pandey, Yogesh; Vasundhara, Paikra; Anjali (International Research Journal of Ayurveda & Yoga, 2025)
In Introduction: Jeevaniya Mahakashaya is one of the 10 classical groupings of herbs described by Acharya Charaka in the Charaka Samhita. This formulation includes ten medicinal plants – Jeevaka, Rishabhaka, Meda, Mahameda, Kakoli, Ksheerakakoli, Mudgaparni, Mashaparni, Jeevanti, and Madhuka, known for their rejuvenative, life promoting, and tissue-nourishing properties. Traditionally, these herbs have been integral to Rasayana Chikitsa (rejuvenation therapy) in Ayurveda, with indications in chronic illness, convalescence, and degenerative disorders. Their therapeutic effects are attributed to the enhancement of Ojas (vital essence), promotion of longevity, and improvement of physical and mental vitality. Aims and Objective: This review aims to bridge classical Ayurvedic knowledge with modern scientific insights by analyzing the pharmacological actions and therapeutic potential of the Jeevaniya Mahakashaya group. It seeks to evaluate their individual and synergistic effects to promote holistic health, especially in the areas of immunity, geriatrics, and tissue regeneration. Materials and Methods: A comprehensive review of Ayurvedic classical texts and contemporary scientific literature was undertaken. The focus was on identifying the mechanisms of action, including nourishment of Rasa and Mamsa Dhatus, enhancement of Shukra Dhatu, immune modulation, reduction of oxidative stress, and promotion of tissue regeneration. Key pharmacological activities such as adaptogenic, antioxidant, immunomodulatory, anti inflammatory, and neuroprotective properties were evaluated through modern pharmacological studies. Discussion: Jeevaniya Mahakashaya consists of a group of ten herbs that have been acknowledged in Ayurveda for their profound life-promoting, rejuvenative, and nourishing properties. Conclusion: The therapeutic principles of Balya (strengthening), Brihana (nourishing), and Rasayana (rejuvenating) associated with Jeevaniya Mahakashaya find strong support in contemporary research. These herbs demonstrate promising potential for integration into holistic and integrative healthcare approaches.